ANALISIS PERTIMBANGAN HAKIM DALAM PUTUSAN PENGANIAYAAN YANG MENGAKIBATKAN KEMATIAN (STUDI PUTUSAN NO.419/Pid.B/2025/PN.SRG) - Salsabila Rahma; Sherly Fernanda; Fitri Magfiroh; Muhamad Dzikri Al-Jamas (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the judge’s considerations in adjudicating the criminal act of assault resulting in death as regulated under Article 351 paragraph (3) of the Indonesian Penal Code (KUHP), using the Decision of the Serang District Court Number 419/Pid.B/2025/PN Srg as a case study. The research employs a normative juridical method with a case approach by examining court decisions, statutory provisions, legal doctrines, and relevant literature. The results indicate that the panel of judges declared the primary charge under Article 338 KUHP (murder) unproven due to the absence of intent to take the victim’s life, thereby shifting criminal liability to the subsidiary charge under Article 351 paragraph (3) KUHP. However, several issues were identified in the evidentiary process, particularly concerning the causality between the defendant’s violent acts and the victim’s death, as the post-mortem report (visum et repertum) did not provide a detailed explanation of the mechanism of death. Mitigating factors such as the defendant’s emotional state and his admission of guilt also contributed to the relatively lenient sentence of 4 years and 6 months of imprisonment. This study concludes that the judge’s considerations in this case have not fully demonstrated a comprehensive analysis of causality and proportionality in sentencing, highlighting the need for further evaluation of judicial standards in adjudicating assault cases resulting in death.